Anticipating recurrent ischemic events after an acute coronary syndrome: validation and application of the SMART-REACH score. (14th October 2021) - Gomes, D; Presume, J; Albuquerque, F; Lopes, P; Sousa Paiva, M; Reis Santos, R; Aguiar, C; Ferreira, J; Trabulo, M; Mendes, M
Abstract: Background: The SMART-REACH score (SRS) was developed to predict the risk of major adverse cardiovascular events in ambulatory patients with established cardiovascular disease, although it has not been extensively validated. Patients at higher risk of recurrent ischemic events may benefit from novel, more intensive treatment options, and earlier identification of these patients can potentially improve outcomes. Purpose: We aimed to validate the SRS and evaluate its performance in a population recently admitted with acute coronary syndrome. Methods: In this single-centre retrospective cohort, we included 320 patients aged 45 to 80 years, who were discharged following admission for an acute coronary syndrome between 2016 and 2018. To calculate the SRS for each patient, we considered clinical data on admission (age, gender, smoking, diabetes, prior history of vascular disease, heart failure or atrial fibrillation), lipid values obtained within the first 24 hours of hospitalization, serum creatinine level at baseline and once the patient was deemed clinically stable, and discharge medication. The outcome of interest was defined as stroke, myocardial infarction or cardiovascular death (MACE) at two years of follow-up. SRS was assessed for discrimination and calibration. Results: Mean age was 63±9 years, and 240 (75%) were male. There was high prevalence of cardiovascular risk factors: 71% had hypertension, 32% had diabetes mellitus, 42% were active smokers and 25% had previously established cardiovascular disease. The outcome of interest was observed in 38 patients (22 cardiovascular deaths, 6 strokes and 14 myocardial infarctions). SRS showed good discrimination of the estimated MACE risk with overall C-statistic of 0.646 (95% CI, 0.554–0.737, p=0.004) (picture 1) and calibration (p-value for the goodness-of-fit test of 0.544). The global estimated risk of MACE at 2-years was 4.8% (3.8%-6.8%). The expected/ observed ratio was 0.56 for the occurrence MACE (picture 2). Conclusions: Over the first two years after discharge from an acute coronary syndrome, one of every 8 patients developed a potentially fatal recurrent ischemic event. The SRS performed reasonably well in discriminating those at highest risk of MACE, suggesting that this score may help select patients at discharge for ad initium more intensive pharmacological therapy. Funding Acknowledgement: Type of funding sources: None.